Monk Lewis : a critical biography - Macdonald, David Lorne, 1955-2010 (University of Toronto Press, 2000)
A modern critical biography of Matthew Gregory Lewis (1775-1818), until now neglected as a cultural figure. This is the first study to consider all of Lewis's works and their connections to his personal and public life.